Cover crop-specific root-derived biopore structure is associated with biopore sheath bacterial facets in compacted soil columns - Peng Xiong; Guilong Li; Zejun Luo; Hao Li; Zhengfu Yue; Yueming Chen; Xiaolin He; Xiong Fang; Jia Liu; Jingjing Peng (Soil and Tillage Research, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

An intelligent prediction of CO2 leakage in underground geological storage sites - Guanliang Zhang; Haoxian Liu; Tao Yang; Zejun He; Lu Zhang; Jiajun Fu; Jiancheng Niu; Farshad Sadeghpour; Mehdi Ostadhassan; Mengdi Sun (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Characteristics of microplastics in soil and throughfall and their relationships with meteorological factors in a temperate forest ecosystem of the Changbai Mountains - Lei Xie; Yingtong Zhou; Guanhua Dai; Xingbo Zheng; Xinchang Kou; Wei Guo; Jiaxin Liu; Junni Wang; Mingkai Leng; Shihan Xu; Xiaoyue Liu; Zejun Tong; et al. (Journal of Hazardous Materials, 2026)

Near-infrared photobiomodulation can alleviate chemotherapy-induced peripheral neuropathy-associated sensory abnormalities - Zejun Ren; Hengtong Fan; Yuhang Chen; Mingke Chang; Shiqiu Jiang; Guoxiong Liu; Yashou Guo; Zhongyu Wang; Lijiang Gu; Dalin He; Lin Yang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

Modeling the evolution of water-environment-economy coupling system with the impacts of inter-basin water transfer project - Danni Jia; Jingwen Zhang; Zejun Li; Maoyuan Feng; Kairong Lin; Xiaohong Chen; Xiaohui Lei; Lixin He; Chao Ma; Jingru Ji (Journal of Hydrology, 2026)

The role of thermal energy in the electrical process of electrically controlled solid propellants - Zejun Hu; Jianjun WU; Zhicheng He; Yu Zhang; Qinhui Peng; Shiqichang Wu; Yuji Chen (Fuel, 2026)

A novel 450 nm blue laser-mediated sinoporphyrin sodium-based photodynamic therapy inactivates Cutibacterium acnes through stress-mediated metabolic alterations - Hengtong Fan; Zejun Ren; Shuqi Chen; Tingting Huang; Guoxiong Liu; Yashou Guo; Yan Zheng; Yifan Cheng; Xing Li; Yibo Mei; Yuhang Chen; Huihui Tuo; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Mechanism and model of current response of hydroxylamine nitrate-based energetic polymer electrolytes under high voltage - Zejun Hu; Jianjun Wu; Zhicheng He; Yu Zhang; Yang Li; Qinhui Peng; Shiqichang Wu (Chemical Engineering Journal, 2025)

Placenta-targeted Treatment Strategies for Preeclampsia and Fetal Growth Restriction: An Opportunity and Major Challenge - Jianjian Cui; Zejun Yang; Ruilin Ma; Wencong He; Hui Tao; Ya’nan Li; Yin Zhao (Stem Cell Reviews and Reports, 2024)
The placenta plays a crucial role in maintaining normal pregnancy. The failure of spiral artery remodeling (SAR) is a key factor leading to placental ischemia and poor perfusion which is strongly associated with obstetric diseases, including preeclampsia (PE) and fetal growth restriction (FGR). Existing interventions for PE and FGR are limited and termination of pregnancy is inevitable when the maternal or fetus condition deteriorates. Considering the safety of the mother and fetus, treatments that may penetrate the placental barrier and harm the fetus are not accepted. Developing targeted treatment strategies for these conditions is urgent and necessary. With the proven efficacy of targeted therapy in treating conditions such as endometrial cancer and trophoblastic tumors, research on placental dysfunction continues to deepen. This article reviews the studies on placenta-targeted treatment and drug delivery strategies, summarizes the characteristics proposes corresponding improvement measures in targeted treatment, provides solutions for existing problems, and makes suggestions for future studies. Graphical abstract

Integrating fecal pollution markers and fluorescence analysis for water quality assessment of urban river - Zejun Liu; Jinlong Yuan; Yingying Lin; Feng Lin; Bingjun Liu; Qidong Yin; Kai He; Xinfeng Zhao; Haoxian Lu (Science of The Total Environment, 2024)

Effects of Multiple High-Dose Methamphetamine Administration on Enteric Dopaminergic Neurons and Intestinal Motility in the Rat Model - Li He; Huihui Zheng; Jilong Qiu; Hong Chen; Huan Li; Yuejiao Ma; Yingying Wang; Qianjin Wang; Yuzhu Hao; Yueheng Liu; Qian Yang; Xin Wang; et al. (Neurotoxicity Research, 2023)

Meta-analysis of microbial source tracking for the identification of fecal contamination in aquatic environments based on data-mining - Zejun Liu; Yingying Lin; Yanhong Ge; Ziyue Zhu; Jinlong Yuan; Qidong Yin; Bingjun Liu; Kai He; Maochuan Hu (Journal of Environmental Management, 2023)

Amine-functionalized cotton for the treatment of oily wastewater - Yiling Ao; Ji'an He; Keming Chen; Mingzhao Zhu; Fan Ye; Liwei Shen; Ying Yang; Xuening Feng; Zejun Zhang; Yuqi Tang; Yuanzhu Mi (Environmental Research, 2023)

Valorization of slow pyrolysis vapor from biomass waste: Comparative study on pyrolysis characteristics, evolved gas evaluation, and adsorption effects - Xiefei Zhu; Zejun Luo; Qiaozhi Zhang; Mingjing He; Daniel C.W. Tsang (Bioresource Technology, 2023)

Synthesis of a low temperature ionic liquid demulsifier and its demulsification mechanism - Liwei Shen; Shi Liu; Ji'an He; Qian Qu; Yuqi Tang; Zejun Zhang; Dong Xiang; Xuemin Yan; Yuanzhu Mi (Fuel, 2023)

Correction to: Construction of HAnW‑based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Construction of HAnW-based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Combination of Electroacupuncture and Constraint-Induced Movement Therapy Enhances Functional Recovery After Ischemic Stroke in Rats - Dong Wang; Lijuan Li; Qing Zhang; Zejun Liang; Liyi Huang; Chengqi He; Quan Wei (Journal of Molecular Neuroscience, 2021)

Structural evolution and late Carboniferous magmatism of the Zhongguai arc in the western Junggar Basin, Northwest China: implications for tectonic evolution of the Junggar Ocean - Di Li; Dengfa He; Yichi Lian; Yu Lu; Zejun Yi (International Geology Review, 2017)